Criminology in Nigeria: history, evolution, and trends - Raufu, Abiodun (Lexington Books, 2024)
"This book examines the diverse landscape of criminology in Nigeria. It offers historical analysis, cultural specificity, and practical insights into Nigerian crime dynamics. The book contributes to global criminological discourse"--